The Influence of English Language Proficiencies on Pragmatic Realization and Strategies of Making Requests by Saudi Arabia’s Efl Learners - Shadi Majed D. Alshra’ah
The present study contributes to inter language pragmatic studies by revealing the relationship between English language proficiency level of Saudi English Foreign Language learners (SEFL) and their pragmatic realization and strategies of making request act. The aims were to investigate the linguistic variability i.e., the relationship between the high achievers in comparison to the low achievers, particularly in making requests besides revealing the situational variability regarding the differences in pragmatic realization of making requests. The theoretical framework underpinning this study is Cross-Cultural Speech Act Realization Pattern (CCSARP) and Brown and Levinson’s politeness theory. Based on the results obtained from the Touchstone Placement Test (TPT), 98 Saudi EFL undergraduate students were divided into 2 main groups – i.e., the high achievers (N=50) and low achievers (N=48). To achieve the aims, research instruments including Discourse Completion Task (DCT), and Scale Response Questionnaire (SRQ) were employed. Data encompasses request strategies on different situations identified in both DCT and SRQ. Data gained from DCT were qualitatively analyzed to identify the pragmalinguistic knowledge such as level of directness, and internal and external modifications. Additionally, quantitative analysis on the scores of the SRQ also included inferential statistical tests to assess the speaker’s knowledge of pragmatic realization (sociopragmatic knowledge) in using request act. Findings indicate there exists a significant impact of different language proficiency levels in realizing request acts. At pragmalingusitic level, High Achievers (HA) employ mostly the hedge performative and query preparatory strategy, while low achievers (LA) mostly employ mood derivable. Additionally, findings on the social variable on using request strategies revealed that HAs were more conscious of the effect of social power and distance in changing their strategy depending on the contextual variables. However, LAs showed less sensitivity to influence social distance and power though there exists a small similarity shown pertaining to their sociopragmatic and pragmalinguistic competence. The results reflect that English language proficiency has a significant influence on the production and comprehension of request strategies among Saudi EFL learners. Hence, it is necessary to benefit from these results to focus on low archivers to strengthen their ability to employ range of request strategies compared to high achievers. Thesis concludes with recommendations and pedagogical implications for instructors and policy makers to include nonconventional indirect, internal, and external modification as mitigated device in their classrooms and curriculum activities.